High Tissue Factor Microparticle Level in Major Thalassemic Patients with Pulmonary Hypertension - Dimmy Prasetya; Pandji Irani Fianza; Erwan Martanto; Teddy Arnold Sihite (Faculty of Medicine Universitas Padjadjaran, 2019)
Objective: To analyze the correlation between tissue factor microparticles (TF-MP) levels and pulmonary hypertension (PH) in adult thalassemic patients. Methods: This study was conducted from September to October 2018, using secondary and primary data. The secondary data consisted of the PH parameter, which was retrieved from a 2017 previous study entitled ‘Clinical Characteristic and Complication due to Iron Overload in Thalassaemic Patients‘in 2017 while the primary data were the TF-MP, which were obtained from the analysis of frozen serum of the same population using ELISA method. The mean pulmonary arterial pressure (mPAP) values were obtained from echocardiography results and PH was defined as mPAP >25 mmHg.Results: Seven (16.7%) major thalassemic patients experienced PH. The median values of TF-MP levels were higher among major thalassemic patients with PH when compared to the non-PH patients (1569 vs 11.5 pg/dL; p=0.023). No significant difference was observed in the median TF-MP levels between subjects with splenectomy and subjects without splenectomy (11.6 vs 12.3 pg/dL; p=0.44). There was also no difference in mPAP values between subjects with splenectomy and subjects without splenectomy (18.0 vs 17.0 mmHg; p=0.663). When the median TF-MP levels among major thalassemic patients were analyzed in terms of correlation with transfusion level, no statistically significant difference was seen between subjects who received sufficient transfusions (≥180 mL/kgbb/year) and those who received insufficient transfusions (<180 mL/kgbb/year) (r= 0.138; p=0.390).Conclusions: There is a positive correlation between the TF-MP levels and PH in adult major thalassemic subjects.